2004
DOI: 10.1111/j.1524-4725.2004.30263.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Changes in Brow Position, Superior Palpebral Crease, Peak Angle of the Eyebrow, and Jowl Surface Area after Volumetric Radiofrequency Treatments to Half of the Face

Abstract: The application of radiofrequency to the face provides quantifiable changes. The brow along the midpupillary line is elevated to a greater degree than the lateral brow. This is consistent with acute angle changes seen in the eyebrow. Improvements in the lower part of the face with radiofrequency application can be quantified by demonstrating a decrease jowl surface. Moreover, these measurement techniques can be useful tools for evaluating other treatment parameters with radiofrequency application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…Prior studies with the original 1-cm tips have shown good results in skin tightening over the forehead, cheeks, periorbital area, jowls, and neck with treatment energies ranging from 58 to 144 J/cm 2 [3][4][5][6]. In the first multicenter trial to evaluate non-ablative, monopolar radiofrequency for skin tightening, Fitzpatrick et al [3] found a baseline to 6-month improvement in 83% of subjects, treating at energies of 58-140 J/cm 2 and an average 68 repetitions (REPS) per treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies with the original 1-cm tips have shown good results in skin tightening over the forehead, cheeks, periorbital area, jowls, and neck with treatment energies ranging from 58 to 144 J/cm 2 [3][4][5][6]. In the first multicenter trial to evaluate non-ablative, monopolar radiofrequency for skin tightening, Fitzpatrick et al [3] found a baseline to 6-month improvement in 83% of subjects, treating at energies of 58-140 J/cm 2 and an average 68 repetitions (REPS) per treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Average treatment fluences were 130 J/cm 2 on the cheek and 110 J/cm 2 on the neck [4]. Moy et al [6] published their findings on the improvements in eyebrow position and cheek laxity in 10 patients using a system of objective measurements. They analyzed jowl surface area changes after splitface treatment with the 1.0 cm tip at fluences from 97 to 143 J/cm 2 [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, results are overestimated and morbidity is minimized [1][2][3][4][5][6][7][8]. Monopolar radiofrequency has also passed the backlash stage in which all of the ''warts'' are discovered [9].…”
Section: Introductionmentioning
confidence: 99%
“…Monopolar radiofrequency has also passed the backlash stage in which all of the ''warts'' are discovered [9]. We write this article describing how monopolar radiofrequency is used in our practice as it has settled in to a steady state and we better understand its benefits and limitations [2,4,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%